The Influence of Organic and Inorganic Fertilizers on the Growth and Yield of Green Bean, Phaseolus vulgaris L. Grown in Dry and Rainy Season - Mudji Santosa; Moch. Dawam Maghfoer; Hagus Tarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Research aimed to study the influence of organic and inorganic fertilizers on growth and yield of green bean (Phaseolus vulgaris L.). It was conducted in Andisol soil, Batu, East Java, 900 m above sea level, 24-27⁰C for dry season (from May to July 2013) and rainy season (from January to March 2014). A randomized block design was used to arrange five treatments such as 1) no fertilizers applied; 2) five t ha-1 cow manure; 3) 10 t ha-1 cow manure; 4) 50 kg N ha-1, 150 kg P2O5 ha-1 and 50 kg K2O ha-1; and 5) 100 kg N ha-1, 300 kg P2O5 ha-1 and 100 kg K2O ha-1. All treatments of bean was planted in 4 x 3 m2 of plot size and 25 x 20 cm2 of plant spacing. Treatment of 100 kg N ha-1, 300 kg P2O5 ha-1 and 100 kg K2O ha-1 resulted in the highest growth (plant height, leaf number/plant, and leaf area/plant) and yield of pod fresh weight (12.46 t ha-1, in 2013; 16.51 t ha-1, in 2014). The lowest growth and yield was showed by no fertilizer application (6.23 t ha-1, in 2013; 8.36 t ha-1, in 2014).